2020
DOI: 10.1002/anie.202007886
|View full text |Cite
|
Sign up to set email alerts
|

Fluorination Enhances NIR‐II Fluorescence of Polymer Dots for Quantitative Brain Tumor Imaging

Abstract: Here, we describe a fluorination strategy for semiconducting polymers for the development of highly bright second near‐infrared region (NIR‐II) probes. Tetrafluorination yielded a fluorescence QY of 3.2 % for the polymer dots (Pdots), over a 3‐fold enhancement compared to non‐fluorinated counterparts. The fluorescence enhancement was attributable to a nanoscale fluorous effect in the Pdots that maintained the molecular planarity and minimized the structure distortion between the excited state and ground state,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
125
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(125 citation statements)
references
References 60 publications
0
125
0
Order By: Relevance
“…In recent years, many efforts have been devoted to amplifying the photothermal conversion and enhancing fluorescence brightness of NIR-II dyes. [26][27][28][29][30][31][32] But, searching for PDT-effective dyes excitable by >1000 nm light remains a blank field. The key challenge is not just simply pushing the dyes' absorption into NIR-II regions, but more importantly lies in how to rationally modulate their excited state energy distributions, so as to simultaneously achieve NIR-II fluorescence, PDT, and PTT in a subtle and balanced fashion.…”
mentioning
confidence: 99%
“…In recent years, many efforts have been devoted to amplifying the photothermal conversion and enhancing fluorescence brightness of NIR-II dyes. [26][27][28][29][30][31][32] But, searching for PDT-effective dyes excitable by >1000 nm light remains a blank field. The key challenge is not just simply pushing the dyes' absorption into NIR-II regions, but more importantly lies in how to rationally modulate their excited state energy distributions, so as to simultaneously achieve NIR-II fluorescence, PDT, and PTT in a subtle and balanced fashion.…”
mentioning
confidence: 99%
“…[ 76 ] first reported the organic SPNPs, pDA‐PEG (Figure 2) nanoparticles for cell imaging and blood flow tracking in NIR‐II region. After this, SPNPs have garnered wide attention and been exploited for several biomedical applications in NIR‐II region, including tumor imaging, [ 77–81 ] vascular imaging, [ 82–84 ] and phototherapy. [ 85–88 ] However, since the majority of SPNPs are binary micelles after encapsulated hydrophobic SPs into amphiphilic polymers, [ 76,84,88 ] SPNPs may suffer from dissociation in the blood circulation when concentrations are below critical micelle concentrations, causing aggregation of SPs and poor bio‐distribution of SPNPs.…”
Section: Nir‐ii Fluorescence Imaging Contrast Agentsmentioning
confidence: 99%
“…After this, SPNPs have garnered wide attention and been exploited for several biomedical applications in NIR‐II region, including tumor imaging, [ 77–81 ] vascular imaging, [ 82–84 ] and phototherapy. [ 85–88 ] However, since the majority of SPNPs are binary micelles after encapsulated hydrophobic SPs into amphiphilic polymers, [ 76,84,88 ] SPNPs may suffer from dissociation in the blood circulation when concentrations are below critical micelle concentrations, causing aggregation of SPs and poor bio‐distribution of SPNPs. [ 89,90 ] To address these issues, grafted semiconducting polymer amphiphiles have been developed by introducing hydrophilic groups to SP side chains, such as PFTQ‐PEG, which can assemble in aqueous solutions without dissociation.…”
Section: Nir‐ii Fluorescence Imaging Contrast Agentsmentioning
confidence: 99%
“…Recently, a new fluorination strategy to increase the NIR‐II emission signals and QYs of SNPs was reported by Liu et al [52] . Their results revealed that the fluorination of SPs reduces non‐radiative relaxation by maintaining molecular planarity and minimising structural distortions between the excited and ground state.…”
Section: Semiconducting Polymer‐loaded Polymeric Nanoparticlesmentioning
confidence: 99%